Structural, electronic and mechanical properties of two-dimensional silica SiO2 - Nestor Javier Fajardo Reina (2023)
Structural, electronic and mechanical properties of pristine 2D-SiO 2 bilayer, considering neutral native defects, and substitutional impurities: Al, B and P, and also some topological defects, have been addressed, by employing the Kohn-Sham DFT approach as implemented in SIESTA and VASP softwares. We identify a marked tendency for the appearance of strongly spatially localized defect states in the energy gap and resonances in the valence and conduction bands, with some independence of being shallow or deep within the band gap. This highly located states are consequence of quantum confinement and enhanced Coulombic effects in this 2D system. The 2D-SiO 2 lattice responds locally to the induced deformation in the studied point defects, and we propose low energy structural excitations: scissor and rotation modes as responsible. We believe these soft modes are in deep relation with the mechanical response of 2D-SiO 2 . Oxygen vacancies and single interstitials are found to be amphoteric trapping centers in 2D-SiO 2 . The aluminium impurity induces spin separation, showing a different degree of localization of each spin channel. The Stone-Wales (SW) defect shows an interesting behaviour: it is energetically more feasible to turn both layers than to turn just one. Using the Wu, Zhang and Pantelides’s (WZP) methodology we show that only neutral and negative charged states are allowed in the phosphorus impurity. The 2D-SiO 2 bilayer displays a singular mechanical behaviour: as in the 3D counterpart (α-quartz), exhibits two different elastic linear regimes; and in contrast, 2D-SiO2 exhibits a wide range of elastic response, being able to return to the unstrained ground state starting from large strains in ZZ and AC directions. The energy surface of this system exhibits many available metastable states, and the transit between them can be driven by scissor and rotation degrees of freedom associated with the Si-O-Si bonds. We propose a kind of hyper-elasticity in this material is driven not by usual mechanisms such as formation of dislocations or plastic flow, but by strain-induced transitions, where the system starts a new elastic response from a new minimum offered by the many-minima energy surface.